If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -6 + 12 = -8 + 7x Reorder the terms: -6 + 12 + 6x = -8 + 7x Combine like terms: -6 + 12 = 6 6 + 6x = -8 + 7x Solving 6 + 6x = -8 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 6 + 6x + -7x = -8 + 7x + -7x Combine like terms: 6x + -7x = -1x 6 + -1x = -8 + 7x + -7x Combine like terms: 7x + -7x = 0 6 + -1x = -8 + 0 6 + -1x = -8 Add '-6' to each side of the equation. 6 + -6 + -1x = -8 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = -8 + -6 -1x = -8 + -6 Combine like terms: -8 + -6 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| 4x+5=102 | | 3u+6u+4= | | 9.8t^2+8.95t-29=0 | | 64+5-27= | | 5(x-1)-3x=x+4 | | 8p^2-10p-1=0 | | 58-208=-b+8(-36)+5(-5b) | | x^2-30x-9775=0 | | x+x-5=11 | | 6x+8x=144 | | 81+84+3x=180 | | (3x+5)-11=5x+12 | | 52+52+2x+2x=360 | | 6x-6+12=-8+x | | h=16t+38t+5 | | 4(2-x)=2x+2-8x | | 125+10s=230+7s | | -x-x-x-x=4 | | 5(8m-3)+6=7-6(m-5) | | 3(x+7)=8(x+2) | | x^4-12x^3+54x^2-108x+51=0 | | 4h-14hj+16hj+13hj+15hj-17hj= | | 5x+5(3x-31)=-355 | | 5x^4+3x+7=0 | | 135+x+80=180 | | 12-5t=2 | | 5t+3+2t-6t=1+2 | | 5x+5(x-31)=-355 | | 32=2(l+w) | | 16=208 | | 4p-7=19 | | 2[k-(3k+12)+6]=2(k+6) |